An optogenetic system to control membrane phospholipid asymmetry through flippase activation in budding yeast - Tomomi Suzuki (Nature Portfolio, 2020)
Abstract Lipid asymmetry in biological membranes is essential for various cell functions, such as cell polarity, cytokinesis, and apoptosis. P4-ATPases (flippases) are involved in the generation of such asymmetry. In Saccharomyces cerevisiae, the protein kinases Fpk1p/Fpk2p activate the P4-ATPases Dnf1p/Dnf2p by phosphorylation. Previously, we have shown that a blue-light-dependent protein kinase, phototropin from Chlamydomonas reinhardtii (CrPHOT), complements defects in an fpk1Δ fpk2Δ mutant. Herein, we investigated whether CrPHOT optically regulates P4-ATPase activity. First, we demonstrated that the translocation of NBD-labelled phospholipids to the cytoplasmic leaflet via P4-ATPases was promoted by blue-light irradiation in fpk1Δ fpk2Δ cells with CrPHOT. In addition, blue light completely suppressed the defects in membrane functions (such as endocytic recycling, actin depolarization, and apical-isotropic growth switching) caused by fpk1Δ fpk2Δ mutations. All responses required the kinase activity of CrPHOT. Hence, these results indicate the utility of CrPHOT as a powerful and first tool for optogenetic manipulation of P4-ATPase activity.